Antimicrobial-Loaded Polymeric Micelles Inhibit Enteric Bacterial Pathogens on Spinach Leaf Surfaces During Multiple Simulated Pathogen Contamination Events - Yegin, Yagmur; Perez-Lewis, Keila L.; Liu, Shuhao; Kerth, Chris R.; Cisneros-Zevallos, Luis; Castillo, Alejandro; Akbulut, Mustafa; Taylor, Thomas M. (Frontiers in Sustainable Food Systems, 2021)
Protecting fresh-packed produce microbiological safety against pre- and post-harvest microbial pathogen contamination requires innovative antimicrobial strategies. Although largely ignored in the scientific literature, there exists the potential for gross failure in food safety protection of fresh fruits and vegetables leading to opportunity for multiple produce contamination events to occur during production and post-harvest handling of food crops. The primary objective of this research was to determine the efficacy of plant-derived antimicrobial-loaded nanoparticles to reduce Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium on spinach leaf surfaces whilst simulating multiple pathogen contamination events (pre-harvest and post-harvest). Spinach samples were inoculated with a blend of E. coli O157:H7 and S. Typhimurium, each diluted to ~8.0 log10 CFU/mL. The inoculated samples were then submerged in solutions containing nanoparticles loaded with geraniol (GPN; 0.5 wt.% geraniol), unencapsulated geraniol (UG; 0.5 wt.%), or 200 ppm chlorine (HOCl; pH 7.0), with untreated samples serving for controls. Following antimicrobial treatment application, samples were collected for surviving pathogen enumeration or were placed under refrigeration (5°C) for up to 10 days, with periodic enumeration of pathogen loads. After 3 days of refrigerated storage, all samples were removed, aseptically opened and subjected to a second inoculation with both pathogens. Treatment of spinach surfaces with encapsulated geraniol reduced both pathogens to non-detectable numbers within 7 days of refrigerated storage, even with a second contamination event occurring 3 days after experiment initiation. Similar results were observed with the UG treatment, except that upon recontamination at day 3, a higher pathogen load was detected on UG-treated spinach vs. GPN-treated spinach. These data fill a research gap by providing a novel tool to reduce enteric bacterial pathogens on spinach surfaces despite multiple contamination events, a potential food safety risk for minimally processed edible produce.